(untitled) (International Conference on Education, Psychology and Humanities, 2026)
One of the pressing challenges in contemporary medical education is students’ insufficient active engagement and their limited capacity for independent and critical thinking. Traditional teaching approaches no longer align with rapid technological advancements and the evolving demands of modern healthcare systems. Consequently, the integration of interactive technologies has become a necessity rather than an option.Interactive teaching methods promote active learning, enhance students’ analytical and cognitive abilities, and facilitate the development of learning-cognitive competencies. Ultimately, such approaches contribute to the formation of essential professional skills required of a modern healthcare practitioner.